Evaluation of the Acute and Sub chronic Toxicities of the Methanolic Stem Bark Extract of Spathodea campanulata (P. Beauv.) Bignoniaceae - Kihdze, Tanayen Julius; OC, Ezeonwumelu Joseph; Mayowa, Ajayi Abayomi; Joseph, Oloro; Ghaife, Tanayen Grace; Ojok, Lonzy; Bulus, Adzu; Aeschot, Arthur van; Laekeman, Gert; Ganafa, Agaba Amon (British Journal of Pharmacology and Toxicology, 2015)
Spathodea campanulata (P. Beauv.) Bignoniacea is widely used in Ugandan traditional medicine without having much knowledge on any toxicity data. This study carried out the toxicity profile of its methanolic stem bark extract (SCE) at both acute and sub-chronic levels. A single oral dose administration of SCE at the limit dose of study (5000 mg/kg) did not cause any observable toxic effect or mortality. However, a 90 day oral administration in Wistar rats (200, 400 and 800 mg/kg) resulted in an acceleration of bodyweight increase as indicated by the calculation of percentage bodyweight increments at the doses of study. It had no effect on the relative organ weights considered except an increase on the stomach at the 800 mg/kg dose. Among the biochemical parameters considered (ALT, AST ALP, GGT, creatinine and urea) the only significant (p<0.05) increase was observed with ALT at the 800 mg/kg level. The levels of WBC, RBC, RDW and HCT dropped significantly (p<0.05) at the 800 mg/kg and 400 mg/kg for WBC alone in the SCE-treated groups. There was however a significant elevation (p<0.05) of MCV, MCH, MCHC levels at 800 mg/kg in the treated animals compared to the control group. A histological analysis of the isolated organs (heart, testes, lungs, liver, stomach and kidneys) showed that the heart is the vulnerable organ with myocardial necrosis and hemorrhage occurring at the 400 and 800 mg/kg level following 90 days administration. Acute use of SCE is safe. Therefore, the resultant adverse effects observed on the lone liver enzyme (ALT) and the myocardial tissue at high doses following prolonged administration could be avoided if compliant use could be intermittent
Keywords: LD50; Haematotoxicity; Hepatotoxicity; Histopathology; Rat; Spathodea; Toxicity